A dopamine electrochemical sensor based on a platinum–silver graphene nanocomposite modified electrode. Issue 29 (5th May 2020) - Anuar, Nadzirah Sofia; Basirun, Wan Jeffrey; Shalauddin, Md.; Akhter, Shamima
Abstract : A platinum–silver graphene nanocomposite was synthesized and characterized. A nanocomposite modified electrode was fabricated in order to investigate the electrochemical detection of dopamine. Abstract : A platinum–silver graphene (Pt–Ag/Gr) nanocomposite modified electrode was fabricated for the electrochemical detection of dopamine (DA). Electrochemical studies of the Pt–Ag/Gr nanocomposite towards DA detection were performed by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). The CV analysis showed that Pt–Ag/Gr/GCE had enhanced electrocatalytic activity towards DA oxidation due to the synergistic effects between the platinum–silver nanoparticles and graphene. The DPV results showed that the modified sensor demonstrated a linear concentration range between 0.1 and 60 μM with a limit of detection of 0.012 μM. The Pt–Ag/Gr/GCE presented satisfactory results for reproducibility, stability and selectivity. The prepared sensor also showed acceptable recoveries for a real sample study.